Bio-mimetic synthesis of catalytically active nano-silver using Bos taurus (A-2) urine - Prashant D. Sarvalkar (Nature Portfolio, 2021)
Abstract Herein we have synthesized silver nanoparticles (Ag NPs) using liquid metabolic waste of Bos taurus (A-2 type) urine. Various bio-molecules present in cow urine, are effectively used to reduce silver (Ag) ions into silver nanoparticles in one step. This is bio-inspired electron transfer to Ag ion for the formation of base Ag metal and is fairly prompt and facile. These nanoparticles act as a positive catalyst for various organic transformation reactions. The structural, morphological, and optical properties of the as-synthesized Ag NPs are widely characterized by X-ray diffraction spectroscopy, ultraviolet–visible spectroscopy, scanning electron microscope, Fourier transmission infra-red spectroscopy, and atomic force microscopy. The as-synthesized bio-mimetic Ag NPs show potential activity for several reduction reactions of nitro groups. The Ag NPs were also used for degradation of hazardous dyes such as Methylene blue and Crystal violet with good degradation rate constant.